Costa Rica : First and Second Reviews Under the Extended Arrangement Under the Extended Fund Facility, Request for Extension of the Arrangement, and Rephasing of Purchases-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
On March 1, 2021, the IMF Executive Board approved a 36-month arrangement under the Extended Fund Facility (EFF) with access of SDR 1.23749 billion (335 percent of quota, equivalent to USD 1.778 billion) to support the country's response to the pandemic and its reform efforts toward strong, inclusive, and sustainable growth. The authorities' proactive response to the COVID-19 crisis, combined with sustained export performance, have supported a robust recovery. The outlook remains subject to downside risks, amid tighter global financial conditions, higher commodity prices, and the threat of new COVID variants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Costa Rica